Localiser les recueils, localiser les pièces. Éditorialisation des savoirs géographiques en France au xviie siècle - Maxime Martignon; Mathilde Morinet (Viatica, 2025)
This article proposes to study the collections of geographical pieces published in the French domain in the 17th century by observing what the compilers do with them. The case of a collection published by Augustin Courbé in 1651, during the Fronde, and placed under the patronage of the Dupuy brothers, allows us to observe the activity of a whole network which, over a period of twenty years, built up the geographical pieces as resources before publishing them at an opportune moment – when it seemed possible to bend the monarchy’s colonial policy. Secondly, we look at the various publications of a very short piece, the Relation de la Guiane et de ce qu’on y peut faire. Depending on the collection in which it appears, its significance changes.